Which Factors Are Associated With Reproductive Outcomes of DOR Patients in ART Cycles: An Eight-Year Retrospective Study - Li, Lu; Sun, Bo; Wang, Fang; Zhang, Yile; Sun, Yingpu (Frontiers in Endocrinology, 2022)
Introduction: Women with diminished ovarian reserve (DOR) have lower pregnancy rates and higher cancellation rates when seeking ART; however, which factors are associated with reproductive outcomes and whether AMH is a predictor of ART success remain unclear. Objective: This retrospective study was designed to find out factors associated with reproductive outcomes in DOR patients and then discuss the role of AMH in predicting cycle results among this population. Method: A total of 900 women were included in the study. They were diagnosed with DOR with the following criteria: (i) FSH > 10 IU/L; and (ii)AMH < 1.1 ng/ml; and (iii) AFC < 7. They were divided into different groups: firstly, based on whether they were clinically pregnant or not: pregnant group versus nonpregnant group (comparison 1); secondly, if patients had transferrable embryos (TE) or not: TE versus no TE group (comparison 2); thirdly, patients undergoing embryo transfer (ET) cycles were divided into pregnant I and nonpregnant I group (comparison 3). The baseline and ovarian stimulation characteristics of these women in their first IVF/ICSI cycles were analyzed. Logistic regression was performed to ascertain factors associated with clinical pregnancy. Results: Of the 900 DOR patients, 138 women got pregnant, whereas the rest did not in their first IVF/ICSI cycles. AMH was an independent predictor of TE after adjusting for confounding factors (adjusted OR: 11.848, 95% CI: 6.21–22.62, P < 0.001). Further ROC analysis was performed and corresponding AUC was 0.679 (95% CI: 0.639–0.72, P < 0.001). Notably, AMH level of 0.355 had sensitivity of 62.6 percent and specificity of 65.6 percent. Multivariate logistic regression showed female age was associated with clinical pregnancy in ET cycles, women who were under 35 years old were more likely to be pregnant compared to those older than 40 years old (adjusted OR:4.755, 95% CI: 2.81–8.04, P < 0.001). Conclusion: AMH is highly related to oocyte acquired rate and TE rate, and 0.355 ng/ml was a cutoff value for the prediction of TE. For DOR patients who had embryo transferred, AMH is not associated with clinical pregnancy, whereas female age is an independent risk factor of it.